1990
DOI: 10.1212/wnl.40.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Dementia lacking distinctive histologie features

Abstract: From a series of 460 dementia patients referred to a regional brain bank, 14 (3%) patients had a pathologic diagnosis of primary degeneration of the brain involving multiple sites (frontoparietal cortex, striatum, medial thalamus, substantia nigra, and hypoglossal nucleus), with cell loss and astrocytosis. There were no neuronal inclusions and essentially no senile plaques. This entity, which we have termed "dementia lacking distinctive histology" (DLDH), presented with memory loss and personality changes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
170
1
11

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(190 citation statements)
references
References 25 publications
8
170
1
11
Order By: Relevance
“…Many cases of "dementia lacking distinctive histology" (Knopman et al 1990) have subsequently been shown to exhibit positive immunostaining for ubiquitin (Josephs et al 2004;Lipton et al 2004;Mackenzie et al 2006c). In our series, brain tissue was available in 13 cases.…”
Section: Neuropathologic Considerationsmentioning
confidence: 99%
“…Many cases of "dementia lacking distinctive histology" (Knopman et al 1990) have subsequently been shown to exhibit positive immunostaining for ubiquitin (Josephs et al 2004;Lipton et al 2004;Mackenzie et al 2006c). In our series, brain tissue was available in 13 cases.…”
Section: Neuropathologic Considerationsmentioning
confidence: 99%
“…Pathologically, the FTLD spectrum of diseases has been associated with classic Pick's disease with tau inclusions (Pick's bodies;Graff-Radford et al, 1990;Kertesz et al, 1994), FTLD with ubiquitin-onlyimmunoreactive neuronal changes (Jackson et al, 1996;Josephs et al, 2004), dementia lacking distinctive histology (DLDH; Turner et al, 1996;Rossor et al, 2000;Snowden et al, 1992) and neurofilament inclusion body disease (Jaros et al, 2000;Cairns et al, 2003). Subcortical involvement is also common and in nearly 80 percent of all cases of DLDH there is involvement of the midbrain (Knopman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It was more recently recognized that the majority of clinical Pick's disease do not have actual Pick body pathology thereby creating nosological confusion. 44 The authors feel that a histologically based definition of Pick's disease cannot provide an acceptable framework for clinicians. It fosters the idea that this disease is rare and it is not diagnosable in vivo, neither of which is correct.…”
Section: Pick Complex or Frontotemporal Degenerationsmentioning
confidence: 99%